Digest: Exposing the role of rare alleles in inbreeding depression in monkeyflower. (1st March 2020) - Hudson, Asher I.
Abstract: Outcrossing is maintained in many hermaphroditic species despite theoretical work suggesting that alleles increasing selfing should invade outcrossing populations. Brown and Kelly (2019) identify reasons why this may not have occurred in an outcrossing population of monkeyflower, namely that inbreeding depression causes strong reductions in fitness, resulting in selection for the maintenance of outcrossing. They find that genetic load imposed by rare alleles is inversely correlated with fitness‐associated traits, providing evidence that recessive, deleterious alleles contribute to inbreeding depression.